2014
DOI: 10.1080/01621424.2014.999902
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Value of Volunteer-Assisted Community-Based Aging Services: A Case Example

Abstract: This study demonstrates the use of a social return on investment (SROI) approach in estimating the financial and social value created by volunteer-assisted community-based aging services. An expanded value added statement (EVAS) analysis found that the total value of outputs produced by the Concierge Club of San Diego substantially exceeded the cost of the program, after considering likely secondary and tertiary benefits for a range of affected stakeholders-including elderly service recipients, family members,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Of the eight SROI studies, the majority were undertaken in developed nations with half conducted in the UK, two in Canada and one each in the USA and Kenya. One intervention was aimed at children,25 two at pregnant or post-partum women,26 27 two at adults overcoming addiction,28 29 one at adults and families transitioning from homelessness30 and two at older people 31 32. In conducting their analysis, all but one study31 referred extensively to the Guide to SROI 12…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the eight SROI studies, the majority were undertaken in developed nations with half conducted in the UK, two in Canada and one each in the USA and Kenya. One intervention was aimed at children,25 two at pregnant or post-partum women,26 27 two at adults overcoming addiction,28 29 one at adults and families transitioning from homelessness30 and two at older people 31 32. In conducting their analysis, all but one study31 referred extensively to the Guide to SROI 12…”
Section: Resultsmentioning
confidence: 99%
“…Potentially, due to the limitations imposed by resource constraints, it was observed that data were gathered from a limited number of stakeholder groups in many studies, most commonly intervention beneficiaries, though inclusion of some other groups was noted: families or carers,25 32 volunteers25 26 32 and paid staff 25 30 31. One exception was Goudet et al , whose study included a broad range of stakeholders and a large sample size (over 400) including beneficiaries, different types of family members, healthcare providers and local businesses 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Volunteer training has been shown to foster protective factors, with arthritis peer support volunteers demonstrating better self-efficacy in arthritis self-management and decreased depressed mood posttraining [31]. Volunteering also has an economic impact on the health care system: in studies of hospital and community-based volunteers the value of the benefits volunteers provided substantially exceeded the costs of running the volunteer programs [32][33][34]. Volunteer work is a crucial element that supports problem-solving worldwide, supporting individuals, communities, and organizations through unpaid, non-compulsory work [35].…”
Section: Introductionmentioning
confidence: 99%
“…The current SROI method further includes principles and processes typically used in evaluations of economic and financial return on investment [26]. The SROI method has not been applied to the management of MS previously, however, the methodology has been used in the area of neurology [27,28], as well as other areas such as dermatology, cardiology, rheumatology, and oncology within the SNHS [29][30][31][32][33], and other health-related areas in other countries (nephrology [34], old age [35,36], or maternity [37,38], among others [39,40]).…”
Section: Introductionmentioning
confidence: 99%